Evaluating and using observational evidence: the contrasting views of policy makers and epidemiologists - Lily O'Donoughue Jenkins; Paul Michael Kelly; Paul Michael Kelly; Nicolas Cherbuin; Kaarin J Anstey (Frontiers Media S.A., 2016)
Background: Currently, little is known about the types of evidence used by policy makers. This study aimed to investigate how policy makers in the health domain use and evaluate evidence and how this differs from academic epidemiologists. By having a better understanding of how policy makers select, evaluate and use evidence, academics can tailor the way in which that evidence is produced, potentially leading to more effective knowledge translation.Methods: An exploratory mixed-methods study design was used. Quantitative measures were collected via an anonymous online survey (n= 28), with sampling from three health-related government and non-government organisations. Semi-structured interviews with policy makers (n=20) and epidemiologists (n=6) were conducted to gather qualitative data. Results: Policy makers indicated systematic reviews were the preferred research resource (19%), followed closely by qualitative research (16%). Neither policy makers nor epidemiologists used grading instruments to evaluate evidence. In the web survey policy makers reported that consistency and strength of evidence (93%), the quality of data (93%), bias in the evidence (79%) and recency of evidence (79%) were the most important factors taken into consideration when evaluating the available evidence. The same results were found in the qualitative interviews. Epidemiologists focused on the methodology used in the study. The most cited barriers to using robust evidence, according to policy makers, were political considerations (60%), time limitations (55%), funding (50%) and research not being applicable to current policies (50%). Conclusion: The policy makers investigated did not report a systematic approach to evaluating evidence. Although there was some overlap between what policy makers and epidemiologists identified as high quality evidence, there was also some important differences. This suggests that the best scientific evidence may not routinely be used in the development of policy. In essence the policy making process relied on other jurisdictions' policies and the opinions of internal staff members as primary evidence sources to inform policy decisions. Findings of this study suggest that efforts should be directed towards making scientific information more systematically available to policy makers.